Increasing Helicobacter pylori clarithromycin resistance in Australia over 20 years. Issue 9 (19th August 2022) - Schubert, Jonathon P.; Warner, Morgyn S.; Rayner, Christopher K.; Roberts‐Thomson, Ian C.; Mangoni, Arduino A.; Costello, Sam; Bryant, Robert V.
Abstract: Background: Helicobacter pylori infection is responsible for considerable morbidity and mortality worldwide, and eradication rates are falling in many countries, primarily due to clarithromycin and metronidazole resistance. Aims: There is a paucity of contemporary Australian data, which we sought to address by evaluating local rates of resistance of H. pylori to amoxicillin, clarithromycin, metronidazole and tetracycline over the past 20 years. Methods: All gastric biopsy specimens collected at endoscopy to detect H. pylori infection at a single centre underwent routine culture and antibiotic susceptibility testing between 1998 and 2017. Specimens from 12 842 patients were cultured for H. pylori, of which 1473 positive cultures were tested for antibiotic susceptibility. Results: Antibiotic resistance to clarithromycin increased by 3.7% per year (incidence rate ratio [IRR] 1.037; P = 0.014) over 20 years, with a corresponding 5.0% annual increase in minimum inhibitory concentration (MIC) (odds ratio 1.050; P < 0.001). Since 2010, average clarithromycin resistance has exceeded 20%, with >25% of isolates resistant in the past 2 years of data capture. In contrast, rates of resistance to metronidazole (35.3%), amoxicillin (0.14%) and tetracycline (0.34%) and their MIC have remained stable. Review of a representative sample ( n = 120; 8%) of these patients revealed that only 5% had documented prior H. pylori eradication therapy. Conclusions: Over the past 20 years there has been a substantial rise in clarithromycin resistance, with stable metronidazole resistance and low rates of resistance to amoxicillin and tetracycline. Current first‐line H. pylori eradication therapy may fail to achieve adequate eradication rates, and optimal first‐line therapy in Australia should be revisited.